Neurosurgery and Manned Spaceflight. Issue 3 (8th November 2018) - Panesar, Sandip S; Fernandez-Miranda, Juan C; Kliot, Michel; Ashkan, Keyoumars
ABSTRACT: There has been a renewed interest in manned spaceflight due to endeavors by private and government agencies. Publicized goals include manned trips to or colonization of Mars. These missions will likely be of long duration, exceeding existing records for human exposure to extra-terrestrial conditions. Participants will be exposed to microgravity, temperature extremes, and radiation, all of which may adversely affect their physiology. Moreover, pathological mechanisms may differ from those of a terrestrial nature. Known central nervous system (CNS) changes occurring in space include rises in intracranial pressure and spinal unloading. Intracranial pressure increases are thought to occur due to cephalad re-distribution of body fluids secondary to microgravity exposure. Spinal unloading in microgravity results in potential degenerative changes to the bony vertebrae, intervertebral discs, and supportive musculature. These phenomena are poorly understood. Trauma is of highest concern due to its potential to seriously incapacitate crewmembers and compromise missions. Traumatic pathology may also be exacerbated in the setting of altered CNS physiology. Though there are no documented instances of CNS pathologies arising in space, existing diagnostic and treatment capabilities will be limited relative to those on Earth. In instances where neurosurgical intervention is required in space, it is not known whether open or endoscopic approaches are feasible. It is obvious that prevention of trauma and CNS pathology should be emphasized. Further research into neurosurgical pathology, its diagnosis, and treatment in space are required should exploratory or colonization missions be attempted.